SOCIO-ECONOMIC DEVELOPMENT OF PERSONAL PEASANTS HOUSEHOLDS - Коваль, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article states that personal peasants households play a significant role in the development of the State food security and serve as an important source for providing the population with valuable and nutritional food-stuffs. It was proved that a multifaceted operation of PPH has some impact on the socio-economic processes in the society; and the status of their development directly influences the well-being of farmers and rallying families; create contingent interested in increasing of employment; transformation of labor relations and the increase in the volume of agricultural products. It was found that in future personal peasants farms within the public sector will not only retain their capacity and production volume; but also ensure economic growth of production. This particular item gives the opportunity to note that unjustified collapse of the public sector would lead to forced further development of the rural population farms in the country’s regions and strengthening of its food security.